The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/bk-2008-0979.ch034
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Structure-Taste Studies of Sulfamates

Abstract: The effect of sulfamation on known tastants has been investigated using several series of compounds containing a primary amine function namely, nitroanilines, phenylureas and -thioureas and amino acids and peptides. Profund changes in taste took place on sulfamation. The effect of chirality on the taste portfolios of various sulfamates has also been examined by preparing sets of enantiomeric pairs from aliphatic, aliphatic/aromatic and alicyclic/aromatic precursor amines and aminoalcohols. Some interesting tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…7. 167 Another example of little or no stereoselectivity is found in the case of monatin (Fig. PIUTTI, THE ASPARAGINE ENANTIOMERS, SWEET TASTE, AND RECEPTORS four chiral stereoisomers, of which only aspartame is sweet, and the three others being without taste or bitter.…”
Section: Receptors For Sweet Tastementioning
confidence: 99%
See 1 more Smart Citation
“…7. 167 Another example of little or no stereoselectivity is found in the case of monatin (Fig. PIUTTI, THE ASPARAGINE ENANTIOMERS, SWEET TASTE, AND RECEPTORS four chiral stereoisomers, of which only aspartame is sweet, and the three others being without taste or bitter.…”
Section: Receptors For Sweet Tastementioning
confidence: 99%
“…152 Also, when a series of chiral sulfamates containing a single stereogenic carbon center in their structure was examined for taste properties, it was found that in most cases, the configuration had no influence or exerted only a minor effect. 167 Another example of little or no stereoselectivity is found in the case of monatin (Fig. 7), which contains two stereogenic centers and can therefore exist as four chiral stereoisomers.…”
Section: Stereoselectivity In Sweet Taste: the Basicsmentioning
confidence: 99%
“…The topic of cyclamate sweeteners has been reviewed, , and one of these reviews also deals with the sweetener saccharin 14 which is regarded as a sulfa sweetener. The structure–taste aspects of sulfamate sweeteners have also been reviewed . Another cyclic sulfamate sweetener, acesulfame-K 4 , has also been reviewed relatively recently .…”
Section: Sulfamic Acidmentioning
confidence: 99%